Inhibition of Sonic Hedgehog Signaling Suppresses Glioma Stem-Like Cells Likely Through Inducing Autophagic Cell Death - Hung, Hui-Chi; Liu, Chan-Chuan; Chuang, Jian-Ying; Su, Chun-Lin; Gean, Po-Wu (Frontiers in Oncology, 2020)
Glioblastoma (GBM) often recurs after radio- and chemotherapies leading to poor prognosis. Glioma stem-like cells (GSCs) contribute to drug resistance and recurrence. Thus, understanding cellular mechanism underlying the growth of GSCs is critical for the treatment of GBM. Here GSCs were isolated from human U87 GBM cells with magnetic-activated cell sorting (MACS) using CD133 as a marker. The CD133+ cells highly expressed sonic hedgehog (Shh) and were capable of forming tumor spheroids in vitro and tumor in vivo. Athymic mice received intracranial injection of luciferase transduced parental and CD133+ GBM cells was utilized as orthotopic GBM model. Inhibited Shh by LDE225 delayed GBM growth in vivo, and downregulated Ptch1 and Gli1. CD133+ cell proliferation was more sensitive to inhibition by LDE225 than that of CD133- cells. Treatment with LDE225 significantly reduced CD133+-derived tumor spheroid formation. Large membranous vacuoles appeared in the LDE225-treated cells concomitant with the conversion of LC3-I to LC3-II. In addition, LDE225-induced cell death was mitigated in the presence of autophagy inhibitor 3-methyladenine (3-MA). Tumor growth was much slower in Shh shRNA- knockdown mice than in control RNA-transfected mice. Conversely, tumor growth was faster in Shh overexpressed mice. Furthermore, combination of LDE225 and rapamycin treatment resulted in additive effect on LC3-I to LC3-II conversion and reduction in cell viability. However, LDE225 did not affect the phosphorylated level of mTOR. Similarly, amiodarone, an mTOR-independent autophagy enhancer, reduced CD133+ cell viability and tumor spheroid formation in vitro and exhibited anti-tumor activity in vivo. These results suggest that Shh inhibitor induces autophagy of CD133+ cells likely through mTOR independent pathway. Targeting Shh signal pathway may overcome chemoresistance and provide a therapeutic strategy for patients with malignant gliomas.